2001
DOI: 10.1111/j.1151-2916.2001.tb00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Control of a 70% Silicon Nitride– 30% Barium Aluminum Silicate Self‐Reinforced Composite

Abstract: The processing response of a 70% silicon nitride-30% barium aluminum silicate (70%-Si 3 N 4 -30%-BAS) ceramic-matrix composite was studied using pressureless sintering, at temperatures ranging from 1740°C, which is below the melting point of BAS, to 1950°C. The relationship between the processing parameters and the microstructural constituents, such as morphology of the ␤-Si 3 N 4 whisker and crystallization of the BAS matrix, was evaluated. The mechanical response of this array of microstructures was characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…It has been reported that barium enriched concrete exhibits very good compressive strength and abrasion resistance in addition to possessing adequate shielding for X-rays comparable to pure lead (Nathuram, 2000). Similarly, barium based materials, such as barium silicate and barium aluminum silicates for their microstructure as self-reinforced composite (Yu et al, 2001), which also were used as additives in radiopaque fillers for making dental composite resin, and an enhancement of X-ray radiation shielding (Ghosh, 2012). These additional materials, which are responsible for enhancing X-ray shielding properties, are based on one or more of the compositions: barium aluminosilicate, iron phosphates, titanium, calcium, and magnesium.…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that barium enriched concrete exhibits very good compressive strength and abrasion resistance in addition to possessing adequate shielding for X-rays comparable to pure lead (Nathuram, 2000). Similarly, barium based materials, such as barium silicate and barium aluminum silicates for their microstructure as self-reinforced composite (Yu et al, 2001), which also were used as additives in radiopaque fillers for making dental composite resin, and an enhancement of X-ray radiation shielding (Ghosh, 2012). These additional materials, which are responsible for enhancing X-ray shielding properties, are based on one or more of the compositions: barium aluminosilicate, iron phosphates, titanium, calcium, and magnesium.…”
Section: Introductionmentioning
confidence: 98%
“…Recent research results showed that BAS (BaO·Al 2 O 3 ·2SiO 2 ) glass-ceramic could effectively promote the densification of Si 3 N 4 ceramics [3][4][5][6][7]. The resulted BAS/Si 3 N 4 composite exhibited an attractive combination of high strength and high fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…R ECENT work [1][2][3][4][5][6][7][8] has shown that silicon nitride (Si 3 N 4 ) with 30 vol% of barium aluminum silicate (BaO⅐Al 2 O 3 ⅐2SiO 2 , BAS) can be processed to full density without costly high processingpressure requirements. The as-sintered material exhibited an attractive combination of high strength and some level of damage tolerance, with an average flexural strength of ϳ963 MPa at room temperature, along with a rising R-curve response to the initial crack growth and a critical fracture toughness of K IC ϭ 5.4 MPa⅐m 1/2 .…”
Section: Introductionmentioning
confidence: 99%
“…The as-sintered material exhibited an attractive combination of high strength and some level of damage tolerance, with an average flexural strength of ϳ963 MPa at room temperature, along with a rising R-curve response to the initial crack growth and a critical fracture toughness of K IC ϭ 5.4 MPa⅐m 1/2 . 6 BAS readily crystallized to hexacelsian on cooling, which contributed to good high-temperature strength. 6 These properties make the Si 3 N 4 -BAS ceramic-matrix composite particularly interesting for both room-temperature and high-temperature applications.…”
Section: Introductionmentioning
confidence: 99%